Henna stages comeback in Senegal - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
The virtues of Henna (Lawsonia inermis) are well known as a beauty product (colouring for hair, hands and feet) and as a curative (treating cuts and grazes, and skin diseases). It is also used as a colorant in cloth and some traditional food...